Direction of urban expansion in the Bangkok Metropolitan Area, Thailand under the impacts of a national strategy - Trong Nguyen, Can; Nguyen Thi Hong, Diep; Sanwit, Iabchoon (Vietnam Journal of Earth Sciences, 2021)
The Eastern Economic Corridor project (EEC), which spans over three coastal provinces east of the Bangkok Metropolitan Area (BMA), aims to transform Thailand into a developed country progressively. The EEC project promises to influence its territory and surrounding areas. We aimed to monitor the urbanized directions at the BMA during 2015-2017 and explore whether the BMA’s urban expansion trend is related to the EEC. The results revealed that the built-up areas increased by 24,033 hectares (22.8%). The urban districts with high urban density slowly developed, while the rural districts tended to urbanize with a high urbanization rate, approximately 6.8% per year. The BMA urban areas mainly expanded to the east (14.9% per year) and southeast (21.6% per year) under partial impacts from the EEC infrastructure projects. The research findings represent a concept for assessing urban expansion and pointing to the regions of concern, which will be meaningful for urban planning and policymaking.